PERTANGGUNGJAWABAN PIDANA PELAKU PENYALAHGUNAAN ATAS PENERIMAAN PEMBAYARAN PAJAK REKLAME BERJALAN MOBIL TANGKI BEREKLAME (Studi Putusan Pengadilan Tipikor Medan No.10/Pid.Sus.K/2014/PN.Mdn) - Sari Devi Tumanggor; Alvi Syahrin; Madiasa Ablisar; Faisal Akbar Nasution (USU LAW JOURNAL, 2017)
ABSTRACT The state is responsible to keep the interests of its people in prosperity, security, defence and education in life. In performing the responsibility to bring it to reality, the state has its sources of revenue to rely on based on valid constitutional regulations. Tax as one of the state's or provinces' sources of revenue has an important role, and its successful accomplishment is the duty of the authorized tax officials. However, in fact there was a tax official who commited corruption by abusing his authority which then causes state's financial loss. How is the official's responsibility in justifying his act as the state's or province's official who had accepted tax-payment wihout depositing it into province's treasury. Key Word : Criminal responsibility, An abuser’s to accepting tax payment